Comparison of cryoprotectants in hematopoietic cell infusion–related adverse events. Issue 6 (9th April 2022) - Ikeda, Kazuhiko; Minakawa, Keiji; Yamahara, Kenichi; Yamada‐Fujiwara, Minami; Okuyama, Yoshiki; Fujiwara, Shin‐ichiro; Yamazaki, Rie; Kanamori, Heiwa; Iseki, Tohru; Nagamura‐Inoue, Tokiko; Kameda, Kazuaki; Nagai, Kazuhiro; et al.
Abstract: Background: The standard cryoprotectant for human cellular products is dimethyl sulfoxide (DMSO), which is associated with hematopoietic cell infusion‐related adverse events (HCI‐AEs) in hematopoietic stem cell transplantation including peripheral blood stem cell (PBSC) transplantation (PBSCT). DMSO is often used with hydroxyethyl starch (HES), which reduces DMSO concentration while maintaining the postthaw cell recovery. The cryoprotectant medium CP‐1 (Kyokuto Pharmaceutical Industrial) is widely used in Japan. After mixture of a product with CP‐1, DMSO and HES concentrations are 5% and 6%, respectively. However, the safety profile of CP‐1 in association with HCI‐AEs has not been investigated. Study Design and Methods: To compare CP‐1 with other cryoprotectants, we conducted a subgroup analysis of PBSCT recipients in a prospective surveillance study for HCI‐AEs. Moreover, we validated the toxicity of CP‐1 in 90 rats following various dose administration. Results: The PBSC products cryopreserved with CP‐1 (CP‐1 group) and those with other cryoprotectants, mainly 10% DMSO (non‐CP‐1 group), were infused into 418 and 58 recipients, respectively. The rate of ≥grade 2 HCI‐AEs was higher in the CP‐1 group, but that of overall or ≥grade 3 HCI‐AEs was not significantly different, compared to the non‐CP‐1 group. Similarly, after propensity score matching, ≥grade 2 HCI‐AEs were more frequent in the CP‐1 group, but the ≥grade 3 HCI‐AE rate did not differ significantly between the groups. No significant toxicity was detected regardless of the CP‐1 dose in the 90 rats. Conclusions: Infusion of a CP‐1‐containing PBSC product is feasible with the respect of HCI‐AEs.